Pembelajaran Seni Menempel dan Menggunting Alternatif Efektif Stimulasi Kognitif Anak Usia Dini - Suary, Ni Putu Chandra Paramis; Andari, Ida Ayu Made Yuni; Mawarini, Ni Kadek Ayu (Institut Agama Hindu Negeri Gde Pudja Mataram, 2024)
This study examines the implementation of art activities, specifically pasting and cutting, to stimulate cognitive development in early childhood at TK Dwijendra Mataram. A qualitative case study design was employed, incorporating observations, interviews with teachers and parents, and an analysis of supporting documents. Findings indicate that pasting and cutting activities have a significant impact on children’s cognitive development, particularly in terms of focus, decision-making, and basic analytical skills. These activities also promote fine motor skills, such as hand-eye coordination and hand muscle strength, essential for future writing readiness. However, challenges were identified regarding children's technical skills and parental perceptions of safety related to scissor use. Recommendations include enhancing material variety and fostering teacher-parent collaboration to support children’s skills holistically. These findings underscore the importance of simple art activities in advancing the cognitive and socio-emotional development of young children, especially within an exploratory learning context.